2022
DOI: 10.3390/w14132009
|View full text |Cite
|
Sign up to set email alerts
|

Governance and Practices for Achieving Sustainable and Resilient Urban Water Services

Abstract: Urban water services can be considered a part of municipal services, including the technical solution from water source to water treatment and distribution, and also wastewater collection, treatment, and discharge back to natural waters. The main aspect is how comprehensive water services concerning the whole society should be considered in urban development. This article emphasizes the necessary role of water services in community technical services and analyzes its critical functions. To keep urban water ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…With the increasing importance of governance in recent water management practices, there is a need for a bottom-up approach in water management strategies, where citizen-participatory governance takes center stage in identifying and resolving on-site water issues [17,18]. Moreover, in this new system, there is a need for a shift toward on-site-centered processes, including project identification, project implementation, and post-management, to ensure a comprehensive approach.…”
Section: Structural Measuresmentioning
confidence: 99%
“…With the increasing importance of governance in recent water management practices, there is a need for a bottom-up approach in water management strategies, where citizen-participatory governance takes center stage in identifying and resolving on-site water issues [17,18]. Moreover, in this new system, there is a need for a shift toward on-site-centered processes, including project identification, project implementation, and post-management, to ensure a comprehensive approach.…”
Section: Structural Measuresmentioning
confidence: 99%
“…Also, although some studies have identified the impact of interventions targeting Water, Energy, and Food Security on wellbeing, there is a need for research that explores context-specific interventions tailored to the Ghanaian context. This will contribute to the development of effective policies and programs that address the specific challenges faced by households in Ghana [ 30 , 31 ]. Furthermore, wellbeing is a complex and multi-faceted concept, and there is a need for standardized indicators and measurement tools specific to the Ghanaian context.…”
Section: Introductionmentioning
confidence: 99%